2014
DOI: 10.4103/0300-1652.129664
|View full text |Cite
|
Sign up to set email alerts
|

Allergic conjunctivitis in Jos-Nigeria

Abstract: Background:Allergic conjunctivitis (AC) may follow seasonal or perennial pattern. There are climatic and racial risk factors involved in some types of AC. It is more prevalent in warm climatic conditions and among Afro-Caribbeans, Arabs and Asians and less among the White populations. Clinical presentations also seem to follow climatic and genetic predisposition. The purpose of this study is to determine the prevalence of AC and its clinical presentations in a hospital setting in this region in people of all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 16 publications
(37 reference statements)
5
26
3
Order By: Relevance
“…The usual presentation of AC includes bilateral intense itching, lacrimation, redness, swollen eyelids, burning sensation with photophobia. [7,8] These are similar to what was found in our patients. The eye features and the treatment offered to our patients are highlighted in Table 1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The usual presentation of AC includes bilateral intense itching, lacrimation, redness, swollen eyelids, burning sensation with photophobia. [7,8] These are similar to what was found in our patients. The eye features and the treatment offered to our patients are highlighted in Table 1.…”
Section: Discussionsupporting
confidence: 91%
“…AC when co-existed with AR and allergic is referred to as Allergic Rhinoconjunctivitis. [6,8] An allergic Rhinitis and allergic conjunctivitis disorder follow a pattern of seasonal and perennial forms, although, the pattern of nasal symptoms is mostly of perennial type with a peak incidence during the dry season while the pattern of ocular symptoms is mostly of seasonal type with a peak incidence during the rainy season. [9,10] Correlating the nasal and eye features of our patients revealed that Eye itching was found to be higher among those with nasal blockage, sleep disturbance, post nasal drip, and nasal polyps( Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed slight predominance of male patients (53.1%) which is lower than that reported by Nagrale and coworkers 15 (82.5%). While female preponderance was reported by Kosrirukvongs et al 13 and also by Malu 16 as 51.2% females among patients with allergic conjunctivitis. Regarding SPT pattern of sensitization, in the present study all allergic patients showed polysensitization pattern for at least 6 allergens.…”
Section: Discussionmentioning
confidence: 80%
“…Allergic conjunctivitis was diagnosed by symptoms of bilateral itchiness and either burning sensation, tearing, ropy/clear mucinous discharge, or photophobia. The ocular signs hinged on the presence of at least two of these: papillae, redness, brownish limbal hyperpigmentation, visible limbal tranta spots and chemosis [ 22 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…While there is a preponderance of hospital-based prevalence studies of AC in Ghana [ 20 , 21 ] and Africa [ 22 , 23 ], the same could possibly not be said of community-based studies. Accordingly, this study, virtually the first Ghanaian community-based studies, had the purpose of determining the prevalence of AC among basic school children in the Kumasi Metropolis together with identifying its main presenting symptoms.…”
Section: Introductionmentioning
confidence: 99%